1994
DOI: 10.1111/j.1365-2249.1994.tb06616.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression patterns of Fcγ receptors, HLA-DR and selected adhesion molecules on monocytes from normal and HIV-infected individuals

Abstract: SUMMARY The expression and co‐expression profiles of functionally important monocyte surface markers were compared between control and HIV+ individuals using combined physical gating and dim CD4 expression to delineate the monocytes. The FcγRII (CD32), the MHC class II antigen HLADR and the adhesion molecules CDIIa (LFA‐1α), CD18 and CD54 (ICAM‐1) showed an unimodal distribution. Of these markers, CDI Ia and HLA‐DR were up‐regulated in the HIV+ subjects compared with controls. The expression levels of the adhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(11 citation statements)
references
References 37 publications
(38 reference statements)
3
8
0
Order By: Relevance
“…An expansion of CD14 + CD16 + monocytes has been observed after HIV-1 infection [10][12] and other inflammatory conditions, while numbers of CD14 ++ monocytes do either not change [11], [13], or decrease slightly [10], in agreement with our observations. It has been assumed that CD14 + CD16 + monocytes are a distinct “proinflammatory” subset of the monocyte lineage [14].…”
Section: Discussionsupporting
confidence: 92%
“…An expansion of CD14 + CD16 + monocytes has been observed after HIV-1 infection [10][12] and other inflammatory conditions, while numbers of CD14 ++ monocytes do either not change [11], [13], or decrease slightly [10], in agreement with our observations. It has been assumed that CD14 + CD16 + monocytes are a distinct “proinflammatory” subset of the monocyte lineage [14].…”
Section: Discussionsupporting
confidence: 92%
“…This cell subset is expanded in several inflammatory diseases such as sepsis, HIV infection, and tuberculosis or in patients with acute or chronic infection undergoing hemodialysis (Nockher and Scherberich 1998) and is selectively suppressed by glucocorticoid therapy (Nockher and Scherberich 1998;Locher et al 1994;Vanham et al 1996;Fingerle-Rowson et al 1998). As this population is responsible for production of higher levels of TNF than the CD14+ monocytes (Calandra and Roger 2003), the increase in TNF level is the same in both groups in our study.…”
Section: Discussionsupporting
confidence: 54%
“…During HIV infection, chronic innate immune activation with expansion of proinflammatory monocyte subpopulations and related cytokine production is only partially returned to normal levels upon the initiation of cART (2,28,(32)(33)(34). In the studies reported in this article, we show that, irrespective of cART, there is also an increase in the percentage of monocytes expressing Glut1 in HIV + individuals when compared with monocytes from HIV 2 individuals.…”
Section: Discussionmentioning
confidence: 53%